수술을 권유 받은 족관절 외측 불안정성의 비수술적 치료 후 5년 이상 추시 결과 - 김태훈(Tae Hoon Kim); 최영락(Young Rak Choi); 박경구(Gyeong Gu Bak) (The journal of the Korean Orthopaedic Association, 2022)
목적: 수술을 권유 받았던 족관절의 외측 불안정성 환자를 대상으로 수술을 시행하지 않고 추시한 환자의 임상적 및 방사선적 추시 결과를 분석하고자 한다. 대상 및 방법: 2009년 5월부터 2016년 12월까지 타 병원에서 수술을 권유 받았으나 본원에서 재활 운동 교육을 1회 시행한 후최단 5년 이상, 평균 7년 이상 의료진 개입 없이 외래 추시하지 않았던 족관절의 외측 불안정성 환자 55명을 대상으로 후향적 연구를 진행하였다. 최종 추시 시 임상적 평가로 이학적 검사와 스포츠 활동을 조사하였고, 시각통증척도(visual analogue scale, VAS), 발 기능 지수(foot function index, FFI), Foot and Ankle Ability Measure (FAAM) 척도를 각각 측정하였다. 재방문한 37 명에 대해서는 진찰 소견의 전방 전위 검사(anterior drawer test)상 불안정성 정도를 평가하였고 체중 부하한 단순 방사선 검사상관절염 진행 여부를 확인하였으며, 스트레스 방사선 검사상 불안정성 여부를 조사하였다. 결과: 55명의 평균 추시 기간은 88.78 (60–136)개월이었고 최종 추시 시 평균 VAS는 0.98 (0–4)이었으며 모두 일상 생활의 제한은 없었다. FFI 점수는 11.27 (1–45), FAAM 점수는 각각 79.35 (일상생활 활동 척도), 27.08 (스포츠 활동 척도)로 호전되었다. 재방문한 37명은 이학적 검사상 전방 전위 검사의 평균 등급은 초진 시 2.08에서 최종 추시 시 2.02로 호전되었다. 방사선 검사상전례에서 족관절의 퇴행성 관절염으로 진행된 경우는 없었다. 해당 병변의 전방 전위 측면 방사선 검사(anterior drawer stress X-ray)의 평균 수치는 초진 시 5.64 mm에서 최종 추시 시 5.47 mm (건측 평균 4.99 mm)로 측정되었다. 내반 스트레스 방사선검사(varus stress X-ray)의 평균 수치는 초진 시 12.03°에서 최종 추시 시 13.62° (건측 평균 10.62°)로 측정되었다. 결론: 타 병원에서 수술을 권유 받았으나 수술을 시행하지 않은 외측 족관절 불안정성 환자의 평균 7년 이상 추시 결과, 기능적인문제가 발생하지 않았으며 방사선 검사상 퇴행성 관절염으로 진행된 경우는 관찰되지 않았다 Purpose: This study analyzed the follow-up results of lateral ankle instability patients without surgery that were recommended surgery from other hospitals. Materials and Methods: From May 2009 to December 2016, a retrospective study was conducted on 55 chronic lateral ankle instability patients at least five years of follow-up and an average of seven years or more. Nonoperative treatment was performed after one time of rehabilitation exercise training at the authors’ hospital. At the final follow-up, a physical examination and sports activity survey were done. Visual analogue scale (VAS), Foot Function Index (FFI), and Foot and Ankle Ability Measure (FAAM) scale were measured, respectively. For 37 patients who revisited, an anterior drawer test was done. In addition, the progression of arthritis was confirmed by a weight-bearing radiographic examination and instability was checked in stress radiographic examination. Results: The average follow-up period of the 55 patients was 88.78 (60–136) months. The average VAS was 0.98 (0–4). None of the patients had restrictions of activities of daily living. For 37 patients who revisited, at the final follow-up, the mean FFI score was 11.27 (1–45), and the FAAM subscale scores were 79.35 (activities of daily living subscale) and 27.08 (sports subscale), respectively. As a result of the physical examination, the mean grade of anterior drawer test decreased from 2.08 at the first visit to 2.02 at the final follow-up. At the final follow-up, radiological examination showed no case of progression of degenerative arthritis of the ankle joint. The average value of anterior drawer stress X-ray was measured from 5.64 mm at the first visit to 5.47 mm (contralateral side 4.99 mm) at the final follow-up, and the average value of varus stress X-ray was measured from 12.03° at the first visit to 13.62° (contralateral side 10.62°) at the final follow-up. Conclusion: In lateral ankle instability patients with nonoperative treatment after an average follow-up of more than seven years, ankle functions were good. There were no cases of progression to degenerative arthritis on radiological examination. KCI Citation Count: 0